2014
DOI: 10.1007/s00384-014-2078-5
|View full text |Cite|
|
Sign up to set email alerts
|

Sacral neuromodulation for faecal incontinence: is the outcome compromised in patients with high-grade internal rectal prolapse?

Abstract: The presence of a high-grade internal rectal prolapse has a detrimental effect on sacral neuromodulation for faecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…The board of experts also shares this view, but refers to a study by Prapasrivorakul et al [15]. In this study it was shown that patients with rectal intussusception (Oxford grade 3,4) exhibit a worse therapeutic outcome than patients without intussusception.…”
Section: Contraindicationsmentioning
confidence: 82%
See 1 more Smart Citation
“…The board of experts also shares this view, but refers to a study by Prapasrivorakul et al [15]. In this study it was shown that patients with rectal intussusception (Oxford grade 3,4) exhibit a worse therapeutic outcome than patients without intussusception.…”
Section: Contraindicationsmentioning
confidence: 82%
“…In patients with fecal incontinence and obstructed defecation syndrome, SNS is a good therapeutic option. Potential restrictions have been illustrated in question 27 [15].…”
Section: Combined Indicationsmentioning
confidence: 99%
“…24 Therefore, the question arises whether correction of the prolapse, e.g. by LVR might be considered as the treatment method for faecal incontinence in patients with high grade internal rectal prolapse with possible neurostimulation added later if the desired effect is not achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dynamic imaging in patients with pelvic fl oor prolapse may better identify patients requiring multi-compartment repair and prevent recurrences [ 136 , 137 ]. Given surgical correction of rectal intussusception (RI) can improve bowel continence [ 138 ], and the possibility that sacral neuromodulation may be less effective in treating fecal incontinence in patients with high grade RI [ 139 ], dynamic imaging is performed routinely in some centers in the evaluation of fecal incontinence.…”
Section: Anatomic and Functional Evaluationmentioning
confidence: 99%